Pengaruh Content Marketing dan Purchase Intention terhadap Pelanggan Shopee di Kabupaten Garut - Ramadhan, Denissa Fitria; Rosa, Aisyah; Aprilianti, Annisa; Yusuf, Ramayani (Journal of Accounting, Management, Economics, and Business (ANALYSIS), 2024)
The study is based on research showing that Shoppee consistently ranks among other e-commerce providers. In response, the researchers took steps to investigate whether content marketing had an impact on Shoppe loyalty. This study is descriptive with a quantitative approach, Data collection was obtained by distributing online questionnaires to all Shopee users in Garut Regency. The sample used in this study was 102 respondents using purposive sampling techniques. Simple regression analysis is used for data analysis of this study, for research results, determination coefficient test, t value test, etc. Data analysis using simple regression analysis yielded the formula Y = 6.768 + 0.761X, and the calculated t value of 13.445 is greater than the table t (13.445 > 1.661) and the Sig value. If it is 0.000, it means that the significance value is lower than the probability value (0.000 < 0.05). Then HO was rejected. We can conclude that content marketing has a significant influence on Shoppe purchase intent.